Esthetic Root Coverage with Double Papillary Subepithelial Connective Tissue Graft: A Case Report - Ramesh Babu Mutthineni; Ram Babu Dudala; Arpita Ramisetty (Case Reports in Dentistry)
Patients today have become excessively concerned about esthetics. These esthetic concerns of patients have become an integral part of periodontal practice. Gingival recession is an esthetic problem that can be successfully treated by means of several mucogingival surgical approaches, any of which can be used, provided that the biologic conditions for accomplishing root coverage are satisfied with no loss of soft and hard tissue height interdentally. There are currently different techniques for root coverage which include pedicle grafts, free gingival grafts, connective tissue grafts, and guided tissue regeneration (GTR). This paper reports a case in which a new double papillary connective tissue graft technique has been used in the treatment of gingival recession.